Security protocols : (Springer, 2005)
This book constitutes the thoroughly refereed post-proceedings of the 11th International Workshop on Security Protocols, held in Cambridge, UK, in April 2003. The 25 revised full papers presented together with edited transcriptions of some of the discussions following the presentations have passed through two rounds of reviewing, revision, and selection. Among the topics addressed are authentication, mobile ad-hoc network security, SPKI, verification of cryptographic protocols, denial of service, access control, protocol attacks, API security, biometrics for security, and others.